2017
DOI: 10.1016/j.bandc.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Social attention in children with epilepsy

Abstract: Children with epilepsy may be vulnerable to impaired social attention given the increased risk of neurobehavioural comorbidities. Social attentional orienting and the potential modulatory role of attentional control on the perceptual processing of gaze and emotion cues have not been examined in childhood onset epilepsies. Social attention mechanisms were investigated in patients with epilepsy (n = 25) aged 8-18 years old and performance compared to healthy controls (n = 30). Dynamic gaze and emotion facial sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…CWEOE fixated the social scene longer than the nonsocial scene, indicating they were more drawn toward social stimuli overall, but they did so significantly less than control children, reflecting a weaker attraction to social stimuli than should be expected. This reduction in attentional priority for socially relevant stimuli in the absence of a clear interaction between group and social functioning T scores, suggests that, like in previous reports, 21 epilepsy itself has an independent and adverse impact on the development of the social brain in early life. Fixation duration to the social scene remained stable across age in CWEOE, and thus the clearest disparity in social attention was observed in the youngest CWEOE.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…CWEOE fixated the social scene longer than the nonsocial scene, indicating they were more drawn toward social stimuli overall, but they did so significantly less than control children, reflecting a weaker attraction to social stimuli than should be expected. This reduction in attentional priority for socially relevant stimuli in the absence of a clear interaction between group and social functioning T scores, suggests that, like in previous reports, 21 epilepsy itself has an independent and adverse impact on the development of the social brain in early life. Fixation duration to the social scene remained stable across age in CWEOE, and thus the clearest disparity in social attention was observed in the youngest CWEOE.…”
Section: Discussionsupporting
confidence: 78%
“…Eye movement analysis of social attention in childhood epilepsy has been scarce, although atypical visual attention toward faces in adolescents with epilepsy as well as epilepsy‐related Rett syndrome has been reported 21‐23 . In adolescents, Lunn et al 21 found slower gaze processing toward emotional expressions that was independently associated with epilepsy, with the authors suggesting that age at epilepsy onset could be associated with age‐dependent social skill acquisition. Social attention status in CWEOE has not been investigated to our knowledge, despite early childhood being a key period in fundamental neural and social development 24,25 .…”
Section: Introductionmentioning
confidence: 99%